2011
DOI: 10.4172/2155-9821.s2-001
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Carbon Source Pre-Adaptation on Clostridium ljungdahlii Growth and Product Formation

Abstract: Syngas fermentation is considered an alternate processing method for biofuel and biochemical production as part of thermochemical biomass conversion. Exposure of syngas fermenting microorganisms to sugars, either in the primary syngas fermentation or through pre-adaptation in the seed culture, has the potential to enhance overall fermentation performance and stress tolerance. In this rapid communication, Clostridium ljungdahlii was grown on different carbon sources including syngas only, syngas-fructose and fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 22 publications
0
9
0
Order By: Relevance
“…lostridium ljungdahlii is a promising chassis for the production of organic commodities and biofuels from syngas and carbon monoxide wastes (1)(2)(3)(4)(5) as well as for microbial electrosynthesis, a process in which electrical energy powers the microbial reduction of carbon dioxide to multicarbon organic compounds (6)(7)(8)(9). One reason that C. ljungdahlii is an attractive catalyst for these processes is that it uses carbon dioxide as an electron acceptor for anaerobic respiration via the Wood-Ljungdahl pathway (7,(10)(11)(12).…”
mentioning
confidence: 99%
“…lostridium ljungdahlii is a promising chassis for the production of organic commodities and biofuels from syngas and carbon monoxide wastes (1)(2)(3)(4)(5) as well as for microbial electrosynthesis, a process in which electrical energy powers the microbial reduction of carbon dioxide to multicarbon organic compounds (6)(7)(8)(9). One reason that C. ljungdahlii is an attractive catalyst for these processes is that it uses carbon dioxide as an electron acceptor for anaerobic respiration via the Wood-Ljungdahl pathway (7,(10)(11)(12).…”
mentioning
confidence: 99%
“…In addition to tolerating various amounts of oxygen, it has been suggested that exposing acetogens to microaerobic conditions triggers a shift in electron flow toward more reduced products, such as ethanol, lactate, H 2 , and/or NH 4 ϩ production instead of acetate formation (51,59,61). C. ljungdahlii was previously shown to grow well and coferment fructose and artificial syngas in a complex medium (5,6,62). Upon exposure to low concentrations of oxygen (Ͻ10%) in the headspace of batch cultures at early log phase, C. ljungdahlii continued to grow and coferment fructose and artificial synthesis gas components while showing an increase in ethanol/acetate ratios (63).…”
mentioning
confidence: 99%
“…For instance, in the acetogen Clostridium ljungdahlii, it has been demonstrated that an adaptation phase, reached by exposing the pre-cultures to CO, could enhance CO stress tolerance. Moreover, in the same study, it was also demonstrated that the combination of CO and a reducing sugar could positively affect the accumulation of both the biomass and the end products, such as ethanol or acetate, due to a higher accumulation of energy (e.g., ATP and GTP), and to the reducing equivalents (e.g., NADH) provided by the sugar metabolism [27].…”
Section: Introductionmentioning
confidence: 80%